PENANGANAN PASCAPANEN SAYUR KANGKUNG HIDROPONIK DI KECAMATAN SUKMAJAYA KOTA DEPOK - Haura Nada Muthmainnah; Vega Yoesepa Pamela; Fitria Riany Eris (Fakultas Pertanian Universitas Tompotika Luwuk, 2024)
In Indonesia, vegetables and fruit are available in various varieties. This is also accompanied by quite high consumption interest. Vegetables and fruit are classified into climacteric and non-climacteric groups. With the high interest in consumption, abundant availability and climacteric properties of vegetables and fruit, a technology is needed that can maintain the quality of the ingredients, namely post-harvest technology. The aim of this research was to determine the post-harvest handling applied to kale vegetables. This research was carried out in a hydroponic-based water spinach garden located on Jl. Majapahit, Sukmajaya District, Depok through the observation and interview stage of one of the hydroponic garden owners who is part of the Mekarbesari Women Farming Community (KWT). Water spinach plants are harvested at the age of 14 days and immediately marketed. After being harvested, the kale vegetables are first sorted. Next, it is weighed, packaged and handed over to consumers. Water spinach vegetables will be harvested after meeting the harvesting age criteria, with the physical appearance of large, strong stems and large leaves. Vegetables that have been harvested are sorted to separate the good parts from the parts that have decreased in quality. The owner does not go through the storage stage. Products handed over to consumers are packaged using plastic, which does not comply with the packaging criteria required to maintain the general shelf life of kale vegetables.